2006
DOI: 10.1016/j.jnoncrysol.2006.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Properties of porous glasses with embedded ferroelectric materials

Abstract: Methods of introducing two ferroelectric materials, viz. NaNO 2 and (CH 3 NH 3 ) 5 Bi 2 Cl 11 (PMACB), into porous glass matrices and the results of dielectric, pyroelectric, thermal expansion and SEM investigations are presented. The best filling degree was achieved for NaNO 2 introduced from the melt, whereas a significantly worse filling effect was achieved for a water solution as the introducing agent. A splitting was observed in the temperature dependence of dielectric permittivity related to the incommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…According to phenomenological and microscopic models, one should expect a negative shift of the ferroelectric phase transition temperature with decreasing particle sizes. Negative size effects were observed in previous studies of NaNO 2 nanoparticles confined within photonic crystals and porous glasses (see 5–8, 10 and references therein). Phase transition temperatures in sodium nitrite embedded into molecular sieves 10–12 were also lower or very close to that in bulk.…”
Section: Discussionmentioning
confidence: 53%
“…According to phenomenological and microscopic models, one should expect a negative shift of the ferroelectric phase transition temperature with decreasing particle sizes. Negative size effects were observed in previous studies of NaNO 2 nanoparticles confined within photonic crystals and porous glasses (see 5–8, 10 and references therein). Phase transition temperatures in sodium nitrite embedded into molecular sieves 10–12 were also lower or very close to that in bulk.…”
Section: Discussionmentioning
confidence: 53%
“…They also noticed that the modulated phase vanished. In a previous work [7] we found that the modulated phase existed in NaNO 2 embedded into porous glasses with a mean pore diameter of 320 nm. NaNO 3 crystals at room temperature belong to the trigonal system with symmetry R3c À D 6 3d ; Z ¼ 2.…”
Section: Introductionmentioning
confidence: 82%
“…-The suppression of the incommensurate phase transition (PT) at decreasing of particle sizes (for large pores) [3] and the crossover of the ferroelectric PT from the first-order PT to the second-order one as a function of pore diameter [4,5] for small particles. -The formation of specific volume "pre-melted state" above T c accompanied by increasing of unit cell volume, RMS ion displacements, sodium ions mobility and conductivity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%